GEOSTATISTICAL STUDY OF SURFACE SOIL PROPERTIES UNDER AN OIL PALM PLANTATION. II. KRIGING - NURUDEEN, O. O.; OYEDELE , D. J.; AINA, P. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Kriging is a technique for optimal estimation of values of continuous random spatial variables without bias at unsampled locations, using structural properties of the semivariogram and an initial set of data values. Selected soil properties were evaluated from samples collected on a 10m x 10m grid from a 100m x 100m plot under oil palm. Soil properties from unsampled points between the grids were estimated by punctual Kriging, using data obtained from sampling and the properties of their semi-variograms. The estimated values for cone index (CI) were found to be statistically close to the true values as determined from data Collected later from points between the grids. Isarithmic maps of the estimates for the soil properties are presented along with those of the raw data.